Preparation, modification, and characterisation of Yolk-shell structure based catalysts for synthetic gas production - Lim, Zi-Yian (2017)
Hydrogen is an emerging energy carrier for oil refining and fuel cell applications. The development of an efficient and stable catalyst to produce hydrogen gas is required for industrial applications. However critical issues in the catalyst that lead to the deactivation of reactions include active metal particle growth and carbon fouling. Industrial catalysts that are frequently overwhelmed by such issues are substituted or re-treated, which is not time and cost efficient. Therefore, developing durable catalysts that are resistant to sintering and carbon fouling remains an area of interest. A novel and anti-agglomeration Ni@yolk-ZrO2 catalyst is first reported in this thesis. A specific study of the ZrO2 hollow shell showed that the varied porosity of the hollow shell contributed to the catalyst’s ability to inhibit the agglomeration of active Ni particles. The steam reforming of methane was selected as the probe study for this catalyst in this research. Before a thorough analysis of the Ni@yolk-ZrO2 catalyst was performed, the systematic synthesis of Ni@SiO2 was studied. The analysis showed that the Ni particle size can be controlled by tuning the synthesis temperature. Water-to-surfactant ratio in the microemulsion was shown to influence the morphology of the Ni@SiO2 particle. The tetraethyl orthosilicate (TEOS) amount added with fractionated dispensing and the amount of NiCl2 were found to have affected the size and morphology of the Ni@SiO2. For the Ni@yolk-ZrO2 sample, the catalyst was characterised by Transmission Electron Microscopy (TEM) and X-Ray Diffraction. TEM was used for morphology analysis, while X-ray Diffraction was performed for phase analysis and crystallite size measurements. Nitrogen adsorption-desorption isotherm was done to measure specific surface area, total pore volume, and the t-plot micropore volume of the samples. Reducibility analysis of the Nickel species of the Ni@yolk-ZrO2 catalyst was carried out using Temperature Programmed Reduction. The anti-agglomeration property of the Ni@yolk-ZrO2 was established from the TEM and X-ray Photoelectron Spectroscopy analysis. Results showed that the active Ni particles were inside the yolk-shell structured framework, which deterred Ni particles from moving onto the surface of the catalyst. Ni particles were found to be stabilised by the abundant volume of pores in the ZrO2 hollow shell. This result indicates that the Ni particles were anchored by the pores and remained stable during the steam reforming of methane. The Ni@yolk-ZrO2 catalyst was tested by varying the volumes of feed (GHSV) and the steam-to-carbon ratio. This catalyst was also subjected to a recyclability test and proved to be better than conventional impregnated Ni/ZrO2 catalysts. The Temperature Programmed Hydrogenation analysis also proofed that the yolk-shell structure framework inhibited higher order of carbon deposits on the Ni@yolk-ZrO2 catalyst. Varying the porosity of the ZrO2 hollow shell was found to affect the performance of the steam reforming of methane. This varied porosity can be achieved by varying the amount of surfactant during the synthesis of Ni@SiO2@ZrO2. X-ray Photoelectron Spectroscopy analysis results showed that the porosity of the ZrO2 hollow shell contributed to the moderately strong hydrothermal stability of the catalyst for the steam reforming of methane. The hollow shell of the ZrO2 was influenced by the instability of the SiO2. TEM analysis of used BrNi-4.8 catalysts showed that the yolk-shell structure framework of the catalyst collapsed. This result suggests that the shell has weak integrity, and proves that the SiO2 was not able to maintain the yolk-shell framework. The results also suggest that the varied porosity of the ZrO2 hollow shell influences the catalysts’ efficiency even though they share the same yolk-shell structure framework. This is likely due to the differences in the pores of each catalyst configuration, which directly affects the Nickel species involved in the catalytic reaction. Finally, it was demonstrated that the Ni@yolk-ZrO2 catalyst exhibits excellent catalytic performance in comparison to conventional catalysts for the steam reforming of methane. Catalytic activity remained stable and achieved a methane conversion of more than 90 % for 150 hours under operating conditions of GHSV of 50400 mL gcat-1h-1 and S/C = 2.5 at 750 oC.